Comparative Study on the Central Place Concepts of the GermanLänder and Recommendations for their Further Development - Greiving, Stefan; Flex, Florian; Terfrüchte, Thomas (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
Central place concepts are an inherent part of all regional plans of the German federal states (the ‘Länder’). These concepts have become increasingly important because regional plans need to be adapted to recent and future demographic changes in order to ensure an adequate provision of services of general interest. This paper analyses the current central place concepts of the Länder and gives recommendations for their further development. The analysis shows that the Länder have developed different approaches in regard to central place concepts, both in terms of definitions, threshold levels of population and accessibility and also their function for guiding future regional development. The paper gives recommendations on how to improve central place concepts and related plan approval procedures. Policy makers and planning authorities should define and seek political approval for overarching goals, from which key analytical indicators would be derived. These indicators should then be used for an empirical analysis, which would finally allow designating central places and their respective functions. Of course, the underlying methodology should be explained in detail within each regional plan. A central place should not be designated on the basis of its current facilities and services, but on the basis of the specific demographic and spatial characteristics and requirements of the surrounding region. Thus two cities with similar central facilities could nevertheless be handled differently by a central place concept because their respective hinterlands have different needs for central places.